Do they know what's at risk? Health risk perception among the Obese - Joachim Winter; Amelie C. Wuppermann (Center for Economic Studies and ifo Institute (CESifo), 2012)
The perception of disease risks and risky health behaviors are closely associated. In this paper, we investigate the accuracy of disease risk perceptions among obese individuals. We compare subjective risk perceptions for various diseases elicited in the American Life Panel (ALP) to individual's objective risks of the same diseases. We find that obese individuals significantly underestimate their 5-year risks of diabetes, arthritis or rheumatism, and hypertension, while they systematically overestimate their 5-year risks of a heart attack and a stroke. Obese individuals are thus aware of some but not all obesity-related risks. For given diseases, we document substantial heterogeneities in the accuracy of expectations across individuals.
Keywords: I10; I18; D84; 330; obesity; health risk; subjective expectations; Körpergewicht; Gesundheitsrisiko; Wahrnehmung; USA